Factors associated with body weight status among 15-17 year old school-going adolescents in Sibu, Malaysia - Law, Leh Shii (2013)
A tremendous increase was observed in the prevalence of childhood overweight and obesity since a decade ago in both developed and developing countries. A study was conducted to determine factors associated with body weight status among school-going adolescents in Sibu, Sarawak, Malaysia. Sociodemographic, behavioural, psychosocial, and physical environmental factors were assessed by using a self-administered questionnaire. Dietary intake of the students was assessed by 24-hour dietary recall. Weight and height were also measured following standard procedures and body mass index-for-age (BMI-for-age) was determined. The study was conducted among 375 students 15-17 year old who agreed to participate (male: 32.0%, female: 68.0%; Chinese: 39.5%, Iban: 26.4%, Malay: 17.1%, and Melanau: 17.1%; mean age: 16.45 ± 0.53 years old) out of a total of 665 students at four public secondary schools in Sibu (Sarawak). Thus, the response rate was calculated to be 56.4%. Among behavioural factors, two thirds of the students (65.9%) were categorized in low physical activity category (male: 55.8%, female: 70.6%) while only 2.4% (male: 7.5%, female: 0%) were categorized as having a high physical activity level. The mean time spent on sedentary behaviours was 2678.18 ± 850.48 minutes/week (approximately 6.38 hours a day) (male: 2814.13 ± 892.53 minutes/week, female: 2614.20 ± 824.01 minutes/week). For dietary intake, the mean caloric intake was 1777 ± 679 Kcal (male: 1950 ± 678 Kcal, female: 1695 ± 665 Kcal). With regards to psychosocial factors, one fifth of the students (total: 19.7%, male: 18.3%, female: 20.4%) were found to have disordered eating (EAT-26 score equal to or more than 20). Meanwhile, around 42.9% of the students (male: 36.7%, female: 45.9%) were grouped as having low self-regulatory efficacy for physical activity while only 9.9% (male: 11.7%, female: 9.0%) were found to have high self-regulatory efficacy for physical activity. Almost one fifth of the students (total: 22.1%, male: 25.0%, female: 20.8%) were categorized as having low weight management self-efficacy. Still, majority of the students (total: 63.2%, male: 65.0%, female: 62.4%) were found to have moderate weight management self-efficacy. In addition, around one fifth of the students (total: 18.7%, male: 20.8%, female: 17.6%) had low nutrition self-efficacy but majority of them (total: 65.6%, male: 64.2%, female: 66.3%) were found to have moderate nutrition self-efficacy. Regarding body image perception, about half of the students (44.0%) wished to have smaller body size, 27.7% wished to have bigger body size, and 28.3% wished to maintain their body size. Moreover, almost one sixth of the students (total: 14.4%, male: 22.5%, female: 10.6%) had low nutrition knowledge but majority of them (total: 73.6%, male: 68.3%, female: 76.1%) was categorized as having moderate nutrition knowledge. Around 31.2% of the students (male: 36.7%, female: 29.4%) were categorized as having a moderate level of perceived sociocultural pressure while another 2.9% (male: 0%, female: 4.3%) were found to have high perceived sociocultural pressure. For anthropometric measurements, almost 18.6% of the students were found to be overweight and obese (male: 22.5%, female: 16.9%). A low percentage of students (5.0%) were categorized as thin (male: 5.0%, female: 5.1%). Significant differences in the mean scores between male and female students were found in physical activity level (t = 4.241, p = 0.0001), time spent on sedentary behaviours (t = 2.134, p = 0.034), self-regulatory efficacy for physical activity (t =2.111, p = 0.035), weight management self-efficacy (t = -2.270, p = 0.020), and nutrition knowledge (t = -2.003, p = 0.046). The variables, which were found to have significant relationships with body weight status were eating attitudes (r = 0.178, p = 0.001), body discrepancy score (r = 0.645, p = 0.0001), land-use mix-diversity (r = -0.112, p = 0.030), perceived sociocultural pressure to be thin (r = 0.392, p = 0.0001), and breakfast consumption (χ2 = 6.532, p = 0.038). Multiple linear regression analysis showed three factors, namely body discrepancy score (β = 0.576, t = 13.360, p = 0.0001), perceived sociocultural score to be thin (β = 0.150, t = 3.482, p = 0.001), and land-use mix-diversity (β = -0.097, t = -2.490, p = 0.012) were found to be the predictors for body weight status. In conclusion, the present study showed the significant association between body discrepancy score, land-use mix-diversity, and perceived sociocultural pressure to be thin with the body weight status. Future interventions may consider incorporating the identified factors to increase their effectiveness. More studies should be carried out to investigate the interaction between sociodemographic factors, behavioural factors, psychosocial factors, and physical environment factors with body weight status of adolescents.